(untitled) (Global Conference on Multidisciplinary Research and Innovation, 2026)
This thesis examines the role of the population’s financial resources in ensuring the quality of economic growth. The importance of the population’s income, savings and financial assets as a source of investment in the economy is highlighted. The mechanisms of influence of the population’s financial resources on the quality and stability of economic growth through investment processes, consumer demand and financial inclusion are also analyzed. The research results substantiate that the effective involvement of the population’s financial resources in economic processes is an important factor in ensuring the stability and quality of economic growth.